Modification of Medium Composition for Enhancing the Production of Antifungal Activity from Xenorhabdus stockiae PB09 by Using Response Surface Methodology - Chirayu Sa-uth; Paweena Rattanasena; Angsumarn Chandrapatya; Prapassorn Bussaman (International Journal of Microbiology)
Xenorhabdus stockiae PB09 bacterium has been shown to exhibit antifungal activity against several plant pathogens. To improve its efficacy, the optimization of the nutritional components in culture media was performed. The medium components that have significant effects on antifungal activity of X. stockiae PB09 were initially identified using a fractional factorial design. Response surface methodology and central composite design were then used to create a model for optimizing the levels of carbon, nitrogen, and mineral sources that maximize antifungal activity of X. stockiae PB09. After that, the suitable carbon, nitrogen, and mineral sources were selected and adjusted by the second-order polynomial regression model, which predicted that 98.62% of antifungal activity could be obtained when the medium contained sucrose, yeast extract, NaCl, and K2HPO4 at 3.24, 23.71, 5.46, and 2.73 g/L, respectively. Laboratory verification of this recipe resulted in the antifungal activity at 97.95% in the shake flask experiment after 48-hour cultivation, which was significantly 27.22% higher than that obtained by using the TSB medium. In addition, X. stockiae PB09 cultured in the verified recipe by using 5 L fermenter could effectively inhibit the mycelial growth of Phytophthora sp., Rhizoctonia solani, Pythium sp., and Fusarium oxysporum. This study demonstrated that the RSM and CCD were shown to be valuable tools for optimizing the culture medium that maximize the antifungal activity of X. stockiae PB09.